Energetic analyses of installing SOFC co-generation systems with EV charging equipment in Japanese cafeteria. (1st December 2017) - Tanaka, T.; Kamiko, H.; Akiba, K.; Ito, S.; Osaki, H.; Yashiro, M.; Inui, Y.
Highlights: Energetic analyses of installing SOFC CGS with EV charging were performed. Japanese cafeteria was selected as an installation target facility. Merit of SOFC CGS is not optimal when it is backed up by gas water heater. SOFC CGS with heat pump water heater provides much higher energy saving rate. Nighttime-limited electric power supply for EV charging improves system efficiency. Abstract: Energetic feasibility analyses were conducted when an SOFC CGS with EV charging equipment is installed in a facility with a high hot-water demand and a high thermo-electric demand ratio. The university cafeteria located on the Hitachi Campus of Ibaraki University in Japan was selected as an installation target because its electric and hot-water demands fulfilled the intended criterion of a high thermo-electric demand ratio. It was made clear that the merits of a co-generation system are not optimal in the case a gas water heater is selected as the backup hot-water supply. To solve the problems contributing to this bad result and to improve the performance, the authors next selected a heat pump water heater as the backup hot-water supply. It was made clear that this system possesses sufficiently high energy savings performance. It was also shown that the coexistence and co-prosperity of the cafeteria and EV charging equipment are successfully achieved. These results reveal that an SOFC CGS with EV charging equipment can be a feasible candidate for a future energy supply system installed in Japanese cafeteria, which is a facility with a large hot-water demand and a high thermo-electric demand ratio, by adopting a heat pump water heater, instead of the usual gas water heater, as the backup hot-water supply.